2016
DOI: 10.1038/srep37922
|View full text |Cite
|
Sign up to set email alerts
|

A-Kinase Anchoring Protein 4 (AKAP4) is an ERK1/2 substrate and a switch molecule between cAMP/PKA and PKC/ERK1/2 in human spermatozoa

Abstract: Mammalian spermatozoa undergo capacitation and acrosome reaction in order to fertilize the egg. The PKC-ERK1/2 pathway plays an important role in human spermatozoa motility, capacitation and the acrosome reaction. Here we demonstrate that ERK1/2 phosphorylates proAKAP4 on Thr265 in human spermatozoa in vitro and in vivo. Cyclic AMP (cAMP) had no effect on ERK1/2 activity in human spermatozoa, but stimulated the MAPK in mouse pituitary LβT2 gonadotrope cells. cAMP via PKA attenuates PKC-dependent ERK1/2 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…Emerging technologies based on biomolecules capable of predicting fertilization success and pinpointing the causative agents such as oxidative stress that can be targeted to prevent reproductive failure have recently been characterized [ 26 ]. A novel sperm protein and its precursor, AKAP4 and proAKAP4, respectively, have been previously established as molecular markers of sperm quality in different species (mice [ 46 ], stallions [ 47 ], boar [ 48 ], and humans [ 49 , 50 ]) due to their high correlation with sperm motility. AKAP4 and proAKAP4 are the most abundantly expressed proteins of the sperm fibrous sheath in all mammals, being part of the principle piece of the flagellum [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging technologies based on biomolecules capable of predicting fertilization success and pinpointing the causative agents such as oxidative stress that can be targeted to prevent reproductive failure have recently been characterized [ 26 ]. A novel sperm protein and its precursor, AKAP4 and proAKAP4, respectively, have been previously established as molecular markers of sperm quality in different species (mice [ 46 ], stallions [ 47 ], boar [ 48 ], and humans [ 49 , 50 ]) due to their high correlation with sperm motility. AKAP4 and proAKAP4 are the most abundantly expressed proteins of the sperm fibrous sheath in all mammals, being part of the principle piece of the flagellum [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is currently recognized that FSIP1 is a protein involved in sperm flagella assembly and the assembly of A-kinase anchoring protein 4 (AKAP4). AKAP4 can target cAMP-dependent binding protein kinase A (PKA), forming a complex with it, and anchoring PKA to the fibre sheath; studies have reported that AKAP4 is a substrate for ERK1/2 and a protein that catalyses the switch between cAMP/PKA and PKC/ERK1/2 in human sperm[ 24 , 25 ]. It is well known that PKA and PKC play important roles in tumour proliferation, angiogenesis, drug resistance, biological behaviour, and prognosis in colorectal cancer[ 24 , 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since PLC is canonically upstream of PKC, ERK and intracellular calcium mobilization, all signals implicated in the endocannabinoid response, it is also likely an early signal. PKA has conversely been reported to inhibit PKC pathways in other systems (Rahamim Ben-Navi et al, 2016), but cooperative cross-talk between these signaling pathways has also been observed (Gomes and Soares-Da-Silva, 2012; Yao et al, 2008). Src kinase could be acting as an intermediary to allow the PKA signal to activate PLC and, successively, PKC and ERK.…”
Section: Discussionmentioning
confidence: 99%